Family well‐being during the COVID‐19 lockdown in Italy: Gender differences and solidarity networks of care. Issue 1 (13th January 2022) - Rania, Nadia; Coppola, Ilaria; Lagomarsino, Francesca; Parisi, Rosa
Abstract: During the COVID‐19 pandemic, families experienced new challenges related to reorganizing living spaces and the need to renegotiate domestic and care roles. This paper aims to understand how Italian families have reacted to this situation with respect to psychological well‐being, the management of domestic and care activities and solidarity networks of care. The participants were 560 Italian subjects who reported having a parental role. The protocol included a measure of well‐being (the General Health Questionnaire‐12) and some questions related to the time dedicated to domestic activities or to caring for people, the perception of conflict within the family and solidarity networks of care. The data underline how mothers continued to devote more time to home and care activities than fathers, despite the presence of both partners at home during the lockdown. The results also indicate that mothers participated to a greater extent than fathers in solidarity activities, confirming that this dimension is linked to gender. Furthermore, fathers and mothers perceived a lower condition of well‐being in relation to the pre‐pandemic period.